Inferences Between Buridan's Modal Propositions. - Dagys, Jonas; Pabijutaitė, Živilė; Giedra, Haroldas (Problems / Problemos, 2022)
In recent years modal syllogistic provided by 14th century logician John Buridan has attracted increasing attention of historians of medieval logic. The widespread use of quantified modal logic with the apparatus of possible worlds semantics in current analytic philosophy has encouraged the investigation of the relation of Buridan's theory of modality with the modern developments of symbolic modal logic. We focus on the semantics of and the inferential relations among the propositions that underlie Buridan's theory of modal syllogism. First, we review all inferences between propositions of necessity, possibility, contingency, and non-contingency, with or without quod est locution, that are valid in Buridan's semantics, and offer a comprehensive diagrammatic representation that includes them all. We then ask the question if there is a way to model those results in first order modal logic. Three ways of formalizing Buridan's propositions in quantified modal logic are considered. Comparison of inferences between the quantified formulas and Buridan's propositions reveals that, when supplied with a suitable formalization, Buridan's semantics of categorical statements and immediate inferences among them can be fully captured by the quantified modal system T.